Ablation resistance of tungsten carbide cermets under extreme conditions. (December 2020) - Humphry-Baker, Samuel A.; Ramanujam, Prabhu; Smith, George D.W.; Binner, Jon; Lee, William E.
Abstract: A cobalt-free tungsten carbide cermet (WC-FeNi) has been subjected to oxyacetylene flame tests to simulate extreme operating conditions such as a worst-case fusion reactor accident. In such an accident, air-ingress to the reactor may impinge on components operating at surface temperatures in excess of 1000 °C, leading to tungsten oxide formation and its subsequent hazardous volatilisation. Here, the most challenging accident stage has been simulated, where the initial air-ingress could lead to extremely rapid air-flow rates. These conditions were simulated using an oxidising oxyacetylene flame. The separation between flame nozzle and sample was varied to permit peak surface temperatures of 950–1400 °C. When the peak temperature was below 1300 °C, the cermet gained mass due to the dominance of oxide scale formation. Above 1300 °C, the samples transitioned into a mass loss regime. The mass loss regime was dominated by liquid-phase ablation of the scale rather than its volatilisation, which was confirmed by performing a systematic thermogravimetric kinetic analysis. The result was unexpected as in other candidate shielding materials, e.g. metallic tungsten, volatilisation is considered the primary dispersion mechanism. The unusual behaviour of the cermet scale is explained by its relatively low melting point and by the lower volatility of its FeWO4 scale compared to tungsten's WO3 scale. The substantially lower volatility of the WC cermet scale compared to metallic W scales indicates it may have a superior accident tolerance. Abstract : Graphical abstract Unlabelled Image Highlights: Tungsten carbide cermets subjected to nuclear fusion accident scenario conditions. Cermets heated in oxyacetylene flame to 950–1400 °C. At 1300 °C, sample transitioned from mass gain (oxidation) to mass loss (ablation). Dominance of ablation in loss regime due to formation of FeWO4 with low melting point. Volatility of scale is lower than for other shielding materials such as tungsten.